2022
DOI: 10.3389/fcimb.2022.963338
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 severity is associated with population-level gut microbiome variations

Abstract: The human gut microbiome interacts with many diseases, with recent small studies suggesting a link with COVID-19 severity. Exploring this association at the population-level may provide novel insights and help to explain differences in COVID-19 severity between countries. We explore whether there is an association between the gut microbiome of people within different countries and the severity of COVID-19, measured as hospitalisation rate. We use data from the large (n = 3,055) open-access gut microbiome repos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 99 publications
1
14
0
Order By: Relevance
“…These include changes in diversity including stark enrichments and/or loss of specific taxa [27]. Several Studies have focused on differences in the gut microbiome between patients with severe COVID-19 and controls [7,28]. Though these findings are essential, the effect on the larger population, wherein the infection is asymptomatic-to-moderate, is not readily represented.…”
Section: Discussionmentioning
confidence: 99%
“…These include changes in diversity including stark enrichments and/or loss of specific taxa [27]. Several Studies have focused on differences in the gut microbiome between patients with severe COVID-19 and controls [7,28]. Though these findings are essential, the effect on the larger population, wherein the infection is asymptomatic-to-moderate, is not readily represented.…”
Section: Discussionmentioning
confidence: 99%
“…These include changes in diversity [39] including stark enrichments and/or loss of specific taxa [40]. Several Studies have focused on differences in the gut microbiome between patients with severe COVID-19 and controls [7,41,42]. Though these findings are essential, the effect on the larger population, wherein the infection is asymptomatic-to-moderate, is not readily represented.…”
Section: Discussionmentioning
confidence: 99%
“…For the data preprocessing, raw metagenomic reads were first trimmed to the maximal read length of 150 bases using Cutadapt (v3.4) [40]. The preprocessed metagenomic and raw metatranscriptomic reads were processed using IMP: reads were trimmed using Trimmomatic (v.39) [41], reads mapping to the human genome (hg38 genome) or PhiX genome (gi|9626372|ref|NC_001422.1, Enterobacteria phage phiX174 sensu lato, complete genome) were removed using BWA (v. 0.7.9a) [42], and the metatranscriptomic reads were further filtered using SortMeRNA (v.4.2.0-238-g90cdf6c) [43]. In addition, alpha-diversity estimation was performed from metagenomic reads using Nonpareil (v. 3.4.1) [44] as part of the IMP preprocessing step.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…According to Yeoh et al, the differences were found in several gut bacterial diversities of the phyla Bacteroidetes and Actinobacteria between the non-COVID-19 non-FMF people and patients with COVID-19; representatives of the Bacteroidetes were described to be more abundant and Actinobacteria were described to be less in patients with COVID-19 (Yeoh et al, 2021 ). Furthermore, recently, not only the gut commensals with known immunomodulatory potential described to be underrepresented in patients with COVID-19 but also COVID-19 severity in association with population-level gut microbiome variations was discussed (Lymberopoulos et al, 2022 ). These results, in parallel with other studies, highlight the potential utility of multi-kingdom host phenotype and microbiota profiling as a predictive tool for patients with COVID-19 (Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%